2001
DOI: 10.1046/j.1440-6047.2001.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Similar therapeutic serum levels attained with emulsified and oil‐based preparations of coenzyme Q10

Abstract: Studies of the therapeutic efficacy of coenzyme Q10 (CoQ10) have been confounded by the variable bioavailability of numerous CoQ10 preparations. The aims of the present study were to determine the early serum levels attained by two different preparations of CoQ10, a soybean oil-based preparation and a complex micelle emulsion and to assess whether these preparations of oral CoQ10 influence plasma lipid profiles. Twelve healthy individuals received 300 mg CoQ10 daily of either preparation for 7 days in a double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In spite of the suggestion of adapting different formulations over time proposed by some authors, our results are in agreement with Chopra et al . who found a 3.2‐fold increase in bioavailability with solubilized CoQ10 compared with an oil suspension and tablets after a 3‐week supplementation with 120 mg/day.…”
Section: Discussionsupporting
confidence: 93%
“…In spite of the suggestion of adapting different formulations over time proposed by some authors, our results are in agreement with Chopra et al . who found a 3.2‐fold increase in bioavailability with solubilized CoQ10 compared with an oil suspension and tablets after a 3‐week supplementation with 120 mg/day.…”
Section: Discussionsupporting
confidence: 93%
“…It has been recognized that SNEDDS enhanced the bioavailability of several preparations in humans and animals with an increase in its in vitro drug release characteristics [15,16] . However, in some reports, the bioavailability has not increased even though the in vitro dissolution rate or emulsification rate has increased [17,18] . Although there are some reports about anaphylactic reactions to Cremophor, these reactions were observed during intravenous administration, but not during oral administration, based on cytotoxicity studies for SNEDDS oral formulations containing Cremophor [19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…This particular formulation was selected because a previous study had shown a threefold increase in serum levels after only 1 week of therapy 21 . The colour‐matched placebo capsule was identical to the active capsule with the exception of the CoQ 10 .…”
Section: Methodsmentioning
confidence: 99%